E-Government Sophistication of E-Services in Republic of Macedonia - Budinoski, Koste; Trajkovik, Vladimir (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
This paper presents the state of e-Government sophistication in Republic of Macedonia for the period 2007 up to 2010. The survey is done using the 20 basic public e-services. Results showed that further progress will need to be made on two–way interaction. More progress is achieved in G2B (Government-to-business) services, and majority of applications were aimed at facilitating the communication between the government institutions and the business community. We additionally present comparison of online sophistication between Republic of Macedonia and European countries.